2014
DOI: 10.1111/hae.12485
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and health outcomes in persons with haemophilia B

Abstract: Summary Regular participation in physical activity helps to prevent damage and maintain joint health in persons with haemophilia. This study describes self‐reported physical activity participation among a sample of people with haemophilia B in the US and measures its association with health‐related quality of life (HRQoL). Data on 135 participants aged 5–64 years were abstracted from Hemophilia Utilization Group Study Part Vb. The International Physical Activity Questionnaire assessed physical activity among p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
62
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(68 citation statements)
references
References 25 publications
3
62
1
2
Order By: Relevance
“…The oldest age group in our study (55–88 years) experienced an improvement in joint mobility and physical function from 2001 to 2012. However, this group may encounter new clinical challenges due to age-related comorbidities [24], e.g., obesity [25]. We did not include questions on height and weight, which should be included in future research.…”
Section: Discussionmentioning
confidence: 99%
“…The oldest age group in our study (55–88 years) experienced an improvement in joint mobility and physical function from 2001 to 2012. However, this group may encounter new clinical challenges due to age-related comorbidities [24], e.g., obesity [25]. We did not include questions on height and weight, which should be included in future research.…”
Section: Discussionmentioning
confidence: 99%
“…26 The Arabic version of the questionnaire that has been validated with acceptable reliability and validity was used. 26 The Arabic version of the questionnaire that has been validated with acceptable reliability and validity was used.…”
Section: International Physical Activity Questionnaire (Ipaq)mentioning
confidence: 99%
“…26 Scores were calculated by averaging the PA undertaken in the previous week and the PA undertaken in a typical week. 26 Scores were calculated by averaging the PA undertaken in the previous week and the PA undertaken in a typical week.…”
Section: Children's Physical Activity Questionnaire (Cpaq)mentioning
confidence: 99%
“…Over the past years also sport therapeutic treatment options have become a major focus in the treatment of PwH, and their positive effects on health have been described in various studies including pain, range of motion and strength . Niu et al showed that physically active PwH had a better state of health. With regard to HRQoL and self‐confidence, von Mackensen revealed a positive effect of sports therapy .…”
Section: Introductionmentioning
confidence: 99%